2008
DOI: 10.1590/s0100-879x2008001000008
|View full text |Cite
|
Sign up to set email alerts
|

Serogroups and virulence genotypes of Escherichia coli isolated from patients with sepsis

Abstract: Sixty strains of Escherichia coli, isolated by hemoculture, from septicemic Brazilian patients were evaluated to determine their serogroup and invasivity to Vero cells. All 60 patients died within 2 days of hospitalization. Furthermore, the molecular study of the following extraintestinal pathogenic E. coli-associated virulence factor (VF) genes was performed by PCR: i) adhesins: type 1 fimbria (fimH ), S fimbria (sfaD/E ), P fimbria (papC and papG alleles) and afimbrial adhesin (afaB/C ); ii) capsule K1/K5 (k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 21 publications
9
57
2
4
Order By: Relevance
“…It must be stressed that the pharmacological approach is the most favorable way of addressing P2Y 2 protein expression because of the quality of the antibodies. Since several of the P2Y receptors shown to be expressed in the THP-1 cells by mRNA are G xq coupled, we tested whether interference with phospholipase C (PLC) activation and the inositol trisphosphate (IP 3 ATP immediately upon insertion into plasma membranes and THP-1 monocytes express several functional P2 receptors, we expect HlyA to trigger a [Ca 2ϩ ] i response in THP-1 monocytes. Therefore, we exposed fluo-4-AM-loaded THP-1 monocytes to HlyA, which concentration-dependently increased [Ca 2ϩ ] i ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be stressed that the pharmacological approach is the most favorable way of addressing P2Y 2 protein expression because of the quality of the antibodies. Since several of the P2Y receptors shown to be expressed in the THP-1 cells by mRNA are G xq coupled, we tested whether interference with phospholipase C (PLC) activation and the inositol trisphosphate (IP 3 ATP immediately upon insertion into plasma membranes and THP-1 monocytes express several functional P2 receptors, we expect HlyA to trigger a [Ca 2ϩ ] i response in THP-1 monocytes. Therefore, we exposed fluo-4-AM-loaded THP-1 monocytes to HlyA, which concentration-dependently increased [Ca 2ϩ ] i ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…-Hemolysin (HlyA) is an important virulence factor frequently produced by strains of pathogenic Escherichia coli (1)(2)(3). The frequency with which HlyA-producing E. coli strains are isolated from patients increases with severity of the disease (for a review, see reference 2).…”
mentioning
confidence: 99%
“…However, our ST131-O16 isolates lacked the pabB SNPs specific to this clone and likely represent single-locus variants of ST131 within the larger clonal complex, which have been detected here where other molecular assays have failed to do so . By contrast the novel serogroups may have emerged by high-frequency recombination with other E. coli pathotypes, such as uropathogenic, enteroinvasive, enterotoxigenic or enteroaggregative E. coli (Croxen et al, 2013;Ananias & Yano, 2008), highlighting the evolutionary capacity of this particular clone.…”
Section: Discussionmentioning
confidence: 99%
“…The two isolates were of serogroups O1:K1 (patient 1) and O18:K1 (patient 2). Isolates belonging to these serogroups are frequently identified in urinary tract infections, bacteraemia and neonatal meningitis (Ananias & Yano, 2008;Blanco et al, 1996;Croxen & Finlay, 2010). MLST showed that neither strain had any lineage.…”
Section: Discussionmentioning
confidence: 99%